Implementasi Model Role Playing dalam Pembelajaran Bahasa Indonesia dan Pengaruhnya terhadap Keterampilan Berkomunikasi - Nur Lailiyah; Yolanda Rensia Gigik; Avrillya Ainisya; Salma Kurnia Anisa; Mutiara Etikasari (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the implementation of Role Playing learning model in Indonesian language learning and its effect on communication skills of SMAN 6 Kediri students. This research used quantitative approach with quasi-experimental design. The research sample consisted of two classes, namely the experimental class which was given learning using the Role Playing model and the control class which used the Problem Based Learning method. Data collection technique was conducted through speaking skill test, observation of students' participation, and questionnaire of perception towards learning method. The data analysis technique used t-test (independent sample t-test) to measure the difference in communication skills results between the two groups as well as descriptive analysis to see students' responses to the learning model. The results showed that students who learned with the Role Playing model experienced a significant improvement in communication skills compared to the control group. This improvement can be seen from the aspects of fluency in speaking, accuracy in conveying ideas, courage in arguing, and more active interaction in class. In addition, students also showed a more enthusiastic attitude and positive response to learning with the Role Playing model. These findings indicate that the Role Playing model can be an effective strategy in learning Indonesian, especially in improving students' speaking skills and social interaction. Therefore, this model is recommended to be applied in language learning to create a more dynamic and interactive learning atmosphere.